2007
DOI: 10.1002/ppul.20745
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of cardiorespiratory events in infants detected by home memory monitor

Abstract: Summary. In 1,079 infants monitored for >700,000 hr at home for apnea or bradycardia, we found an association between infants having multiple events exceeding conventional or a priori defined more extreme thresholds and less favorable developmental outcome at 1 year of age than infants with few or no events. If it is necessary to prevent such events to minimize risk for developmental morbidity, there is reason to determine whether there are disturbances in advance of the apnea or bradycardia that herald their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…A decreased sympathetic response to tilt testing in infants with ALTE when compared to controls has also been reported [8]. Recently, a study of infants monitored at home documented autonomic instability prior to the event and particularly in the immediate period preceding the event [12].…”
Section: Discussionmentioning
confidence: 94%
“…A decreased sympathetic response to tilt testing in infants with ALTE when compared to controls has also been reported [8]. Recently, a study of infants monitored at home documented autonomic instability prior to the event and particularly in the immediate period preceding the event [12].…”
Section: Discussionmentioning
confidence: 94%
“…Events sufficient to trigger a monitor alarm did not occur de novo but rather were often preceded by respiratory pauses, periodic breathing, and intermittent hypoxemia. 22 It is unclear to what extent the intermittent hypoxemia occurring during non-event epochs has clinical significance only as a potential precursor to events sufficient to trigger a monitor alarm or whether the intermittent hypoxemia occurring in these clinically silent epochs may be contributing to the neurodevelopmental impairments observed in other studies. 10 Future studies in preterm infants will need to better quantify the frequency and severity of intermittent hypoxemia before and after NICU discharge, the relative contribution of each to adverse neurodevelopmental outcome, and the extent to which these adverse outcomes can be ameliorated by intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The British Thoracic Society (BTS) guidelines, 2 in contrast to the ones from Australia and New Zealand, 8 do not generally recommend monitoring during HOT. 9 Poets et al found similar levels of oxygen saturation in healthy preterm infants at the time of hospital discharge (median 99.5%, fifth percentile 95.7%). 2,8 As in 2001, 4 SpO 2 cutoffs for HOT showed a wide range between hospitals from 80% to 94%, with a mean value of 90%.…”
Section: Discussionmentioning
confidence: 83%